2013
DOI: 10.4067/s0718-58392013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presowing gamma irradiation on the photosynthetic pigments, sugar content and carbon gain of Cullen corylifolium (L.) Medik

Abstract: To determine the effects of gamma radiation on the photosynthetic pigments, sugar content and total carbon gain, seeds of Cullen corylifolium (L.) Medik. were irradiated with variable doses (0, 2.5, 5, 10, 15, and 20 kGy) at the rate of 1.65 kGy h -1 from 60 Co gamma source. Cullen corylifolium represents an important Chinese medicine with adequate levels of secondary metabolites, thus we hypothesized that gamma irradiation could modulate primary metabolites which could supplement secondary metabolite levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Treatment with gamma radiation results increment of POD activity but decrement of CAT activity. In this concern, Jan et al [27] reported that gamma radiation increase antioxidant enzymes. Enzyme activation may be due to a modulatory effect of γ -radiation on enzyme structure [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with gamma radiation results increment of POD activity but decrement of CAT activity. In this concern, Jan et al [27] reported that gamma radiation increase antioxidant enzymes. Enzyme activation may be due to a modulatory effect of γ -radiation on enzyme structure [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is a successful method in plant breeding programs. The magnitude effect of gamma (γ) rays depending on its dose and intensity [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll content may either decrease [26] or increase [27] due to irradiation, depending on the species. Low doses of gamma rays enhance chlorophyll synthesis by exciting the enzyme system along with improvement in yield components, while higher doses normally prove inhibitive [1,28,29]. The level of photosynthetic pigments, total carbohydrate, phenols and proline increased significantly due to c-radiation in Vigna sinensis grown under salt stress, thus alleviating the adverse effect of salinity [30].…”
Section: Photosynthetic Traitsmentioning
confidence: 93%
“…Carotenoids plays an important role as detoxicant agents in radiation damage and ROS scavenging (Fukuzawa et al, 1998). An age and dose dependent increase was observed in carotenoids content in Cullen corylifolium leaves being maximum at pre-flowering followed by flowering and post-flowering stages (Jan et al, 2013), even if other studies showed a strong variation of these trends among cultivars of Capsicum annuum L. (Kim et al, 2004).…”
Section: Ionizing Radiation and Photosynthesismentioning
confidence: 68%